Dynamics of reproductive ecology of the fish Ompok bimaculatus (Siluriformes: Siluridae) in six tropical rivers of the Ganges basin, India (UNED Research Journal, 2017)
The silurid butter catfish, Ompok bimaculatus (Bloch, 1794), is widely distributed in the plains and sub-mountain regions of India, but not enough is known about its reproductive potential is still insufficient. The present study evaluated the comparative reproductive potential (in terms of sex ratio, spawning season, body size at first gonadal maturity, gonadosomatic index, fecundity, egg dimension, egg weight etc.) of fish (n=1223) from six tropical tributaries of the Ganges basin during January 2011-December 2013. The females had relatively greater weight and length. The body size at 50% first gonadal maturity (L50%) ranged between 228-262mm in females and 198-247mm in males. The population has high and low fecundities. The correlations between absolute fecundity and total length, as well as between body weight and gonad weight, were significant (p
Keywords: Ganges basin; body size at first gonadal maturity; Ompok bimaculatus; reproductive potential; sex ratio; spawning season